Association of serum interferon‐λ3 levels with hepatocarcinogenesis in chronic hepatitis C patients treated with direct‐acting antiviral agents. Issue 5 (7th February 2019) - Inoue‐Shinomiya, Emi; Murakawa, Miyako; Asahina, Yasuhiro; Nakagawa, Mina; Tsuchiya, Jun; Sato, Ayako; Tsunoda, Tomoyuki; Miyoshi, Masato; Nitta, Sayuri; Kawai‐Kitahata, Fukiko; Itsui, Yasuhiro; Azuma, Seishin; et al.
Abstract : Aim: Although the efficacy of hepatitis C virus (HCV) treatment is improved dramatically by direct‐acting antiviral agents (DAAs), the assessment of hepatocellular carcinoma (HCC) remains important. Interferon lambda 3 (IFN‐λ3) is associated with liver fibrosis and inflammation in chronic hepatitis C (CHC) patients, but its impact on carcinogenesis remains controversial and little is known about its effects after viral clearance. To determine the contribution of IFN‐λ3 to hepatocarcinogenesis after HCV clearance, we analyzed IFNL3 genotypes and serial serum IFN‐λ3 levels in CHC patients who achieved sustained virologic responses (SVR). Methods: This study comprised 201 CHC patients treated with DAAs. Serum samples were collected sequentially and IFN‐λ3 levels were quantified by chemiluminescence enzyme immunoassay. The IFNL3 polymorphism (rs8099917) was genotyped in 195 patients. Results: One hundred and twenty‐five patients were rs8099917 T/T and 70 were non‐T/T. Serum IFN‐λ3 levels did not differ significantly with IFNL3 genotype, dropped markedly by 1 week and remained low up to 24 weeks after the end of treatment. Interferon‐λ3 levels were significantly higher after viral clearance in patients who developed HCC and were associated with a higher potential for hepatocarcinogenesis, such as a higher frequency of non‐hypervascular hypointensive nodules ( P  = 0.046), higher stages of liver fibrosis ( P  < 0.001), and higher post‐treatment levels of Wisteria floribunda agglutinin positive Mac‐2 binding protein ( P  < 0.001) and alanine aminotransferase ( P  < 0.001). Conclusions: Serum IFN‐λ3 levels after HCV clearance are associated with the potential for HCC development. Interferon‐λ3 could be helpful for elucidating the relationships among immunologic status, liver fibrosis, liver inflammation, and hepatocarcinogenesis, after achieving SVR.